Molecular Detection and Typing of Mycobacterium avium Subspecies paratuberculosis from Fecal Samples of Small Ruminants - Dixit, Manu; Filia, Gursimran; Singh, Shur Vir; Islam, Malik Raies Ul (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The chronic nature of Jhone’s disease and prolonged incubation period of the agent often complicate the diagnosis of this disease. The present study was undertaken with an aim to compare fecal microscopy using Ziehl-Nielsen (ZN) staining method and Polymerase Chain Reaction assay for detection of Mycobacterium avium subspecies paratuberculosis (MAP) in small ruminants. A total of 205 fecal samples of sheep and goat were first microscopically examined using ZN staining method and later tested for presence of MAP DNA through IS900 PCR. Win Episcope 2.0 software was used to determine agreement between the test assays. Of the total 205 fecal samples, 78 (38%) were positive by ZN staining method and 48 (23.4%) by IS900 PCR. Moderate level of agreement (0.517) was observed between the test assays. Restriction enzyme analysis of DNA amplicons from IS1311 PCR revealed that all positive samples belonged to Bison type MAP strain. Single predominant strain (Bison type) among all ruminants indicates its ability to infect multiple host species, possibility of interspecies transmission and endemic co-circulation.